Holocene Vegetation and Plant Diversity Changes in the North-Eastern Siberian Treeline Region From Pollen and Sedimentary Ancient DNA - Liu, Sisi; Stoof-Leichsenring, Kathleen R.; Kruse, Stefan; Pestryakova, Luidmila A.; Herzschuh, Ulrike (Frontiers in Ecology and Evolution, 2020)
Although sedimentary ancient DNA (sedaDNA) has been increasingly used to study paleoecological dynamics (Schulte et al., 2020), the approach has rarely been compared with the traditional method of pollen analysis for investigating past changes in the vegetation composition and diversity of Arctic treeline areas. Here, we provide a history of latitudinal floristic composition and species diversity based on a comparison of sedaDNA and pollen data archived in three Siberian lake sediment cores spanning the mid-Holocene to the present (7.6–0 cal ka BP), from northern typical tundra to southern open larch forest in the Omoloy region. Our results show that the sedaDNA approach identifies more plant taxa found in the local vegetation communities, while the corresponding pollen analysis mainly captures the regional vegetation development and has its limitations for plant diversity reconstruction. Measures of alpha diversity were calculated based on sedaDNA data recovered from along a tundra to forest tundra to open larch forest gradient. Across all sites, sedaDNA archives provide a complementary record of the vegetation transition within each lake’s catchment, tracking a distinct latitudinal vegetation type range from larch tree/alder shrub (open larch forest site) to dwarf shrub-steppe (forest tundra) to wet sedge tundra (typical tundra site). By contrast, the pollen data reveal an open landscape, which cannot distinguish the temporal changes in compositional vegetation for the open larch forest site and forest-tundra site. Increasing Larix pollen percentages were recorded in the forest-tundra site in the last millenium although no Larix DNA was detected, suggesting that the sedaDNA approach performs better for tracking the local establishment of Larix. Highest species richness and diversity are found in the mid-Holocene (before 4.4 ka) at the typical tundra site with a diverse range of vegetational habitats, while lowest species richness is recorded for the forest tundra where dwarf-willow habitats dominated the lake’s catchment. During the late Holocene, strong declines in species richness and diversity are found at the typical tundra site with the vegetation changing to relatively simple communities. Nevertheless, plant species richness is mostly higher than at the forest-tundra site, which shows a slightly decreasing trend. Plant species richness at the open larch forest site fluctuates through time and is higher than the other sites since around 2.5 ka. Taken together, there is no evidence to suggest that the latitudinal gradients in species diversity changes are present at a millennial scale. Additionally, a weak correlation between the principal component analysis (PCA) site scores of sedaDNA and species richness suggests that climate may not be a direct driver of species turnover within a lake’s catchment. Our data suggest that sedaDNA and pollen have different but complementary abilities for reconstructing past vegetation and species diversity along a latitude.